Phosphorus Removal by Chemical Precipitation in Wastewater Treatment Plants - Adrian Cabo; Susana Gouveia; Claudio Cameselle; Keun-Heon Lee (Journal of Chemistry)
The EU regulations limit the total phosphorus (P) concentration to 2 mg/L in the discharge effluent from wastewater treatment plants to minimize the negative impacts of nutrients in the ecosystems. This study focuses on monitoring and removal of P in the municipal wastewater treatment plant in Baiona, NW Spain. P is removed in the plant by precipitation as ferric phosphate with the continuous addition of ferric chloride. The FeCl3 dose is adjusted with periodic phosphate analysis in the discharge effluent. This procedure results in a large excess of FeCl3 dosage due to the daily and seasonal variations of P in the wastewater (2.5–8 mg/L). The excess dosage ensures compliance with the P legal limit but increases the consumption of FeCl3 and the associated costs. In this study, we tested the benefits of P concentration monitoring in the discharge effluent with an automated analyzer to optimize the dosage of FeCl3. The automated analyzer determines the P concentration every 2 h and uses this information to adjust the FeCl3 dosage to the real needs. This mode of operation minimizes FeCl3 consumption while ensuring compliance with the legal P discharge limit. Comparing the reagent consumption of 1 year of operation with the previous year with no automated analyzer, the consumption was cut back by 50%. The savings in precipitation reagent can compensate the analyzer installation cost in just 2 years of operation, confirming the rapid return of the investment. Besides, the P precipitation system with the automated analyzer showed stable operation throughout the year under different wastewater flow and P concentration conditions, confirming the system reliability and efficiency in maintaining consistent P removal performance.